Physical and Sensory Characterization of Red Spinach Noodles (Amaranthus tricolor L.) with Drying Temperature Variations - Irmayanti Irmayanti (Serambi Journal of Agricultural Technology, 2020)
The purpose of this research is to obtain a formula of dried noodles with the addition of red spinach and a combination of drying temperature with better nutritional value and can be sensitively accepted. This research consisted of two factors, the addition of red spinach paste (B) consisting of 3 levels, namely: B1: 35%, B2: 40%, B3: 45% and drying temperature (S) consisted of 3 levels, namely S1: 65 oC S2: 70 oC S3: 75 oC. The addition of red spinach paste and drying temperature have an effect on increasing panelist acceptance of dried red spinach noodle products. Based on hedonic organoleptic testing, red spinach dried noodles with the treatment of adding 45% red spinach paste and a drying temperature of 75 oC are the best formulas most favored by panelists. Dry noodles with the addition of 45% red spinach paste and a drying temperature of 75 oC contain water content, ash content, water absorption and taste organoleptic value 4.10 (like), color 4.10 (like), odor 4.30 (like) and texture 4.20 (like ).